Determinants of accounting information system adoption by Small and Medium Enterprises (SMEs) in Kano Metropolis - Rabiu, Naja’atu Bala; Salihu, Maimuna; Maigoshi , Zaharaddeen; Ibrahim, Kabir (Journal of Contemporary Accounting, 2025)
This study examined the determinants of Accounting Information System (AIS) adoption by Small and Medium Enterprises (SMEs) in Kano Metropolis, Nigeria. The adoption of AIS is increasingly viewed as a strategic imperative, particularly in light of the goals outlined in the Nigeria Vision 2030 agenda, as SMEs form the backbone of the Nigerian economy. The study was conducted in Kano Metropolis, with data collected from 297 responses and analyzed using Smart PLS 4.0. The results showed that hypothesis one was supported, while hypotheses two, three, and four were rejected. The findings indicate that facilitating conditions, performance expectancy, and social influence are significant determinants of AIS adoption among SMEs in Kano Metropolis. This suggests that SMEs are more likely to adopt AIS when they perceive the system as beneficial to business performance, have the necessary resources and support, and receive encouragement from influential individuals or groups within their networks. Beyond these results, the originality of this study lies in its application of the full UTAUT framework with PLS-SEM in the Nigerian SME context—a methodological approach not commonly employed in earlier Nigerian studies. Based on these findings, the study recommends that SME owners and managers in Kano Metropolis invest in staff training and digital literacy programs to strengthen their capacity to effectively utilize AIS tools. By fostering a culture of innovation and technological openness, SMEs in Kano can improve financial accuracy, enhance decision-making, and align their operations with Nigeria’s broader digital economy goals under Vision 2030.